Discrete Aurora on Mars: Spectral Properties, Vertical Profiles, and Electron Energies. Issue 10 (8th October 2021) - Soret, Lauriane; Gérard, Jean‐Claude; Schneider, Nicholas; Jain, Sonal; Milby, Zachariah; Ritter, Birgit; Hubert, Benoît; Weber, Tristan
Abstract: We present an analysis of hundreds of middle ultraviolet auroral spectra collected at the limb with the Imaging UltraViolet Spectrograph (IUVS) instrument on board the Mars Atmosphere and Volatile EvolutioN (MAVEN) spacecraft. While the companion paper by Schneider et al. (2021), https://doi.org/10.1029/2021JA029428 focuses on the detection, location, and occurrence frequency of discrete auroral events, this study addresses the spectral properties and vertical profiles of the auroral emissions. Our independent selection of events is based on a combination of automatic and manual detection methods with adequate signal‐to‐noise ratio of both the CO Cameron bands and the CO2 + ultraviolet doublet (UVD) at 190–270 and 288–289 nm, respectively. We find that the ratio of these two features remains quasi‐constant for UVD intensities exceeding ∼200 rayleighs (R), but the CO Cameron/CO2 + UVD ratio may become increasingly large for low UVD intensities. Three weak N2 Vegard‐Kaplan bands are identified in the Martian aurora for the first time. Limb profiles of the [OI] line at 297.2 nm indicate that the visible oxygen green line brightness may reach a few kilorayleighs. The distribution of the altitude of the emission peaks in the aurora is identical in and out of the region of crustal magnetic field located in the southern hemisphere. Comparisons of in situ measurements of electron energy spectra and ultraviolet auroral detections have been made for five optical detections. They generally show temporal coincidence but not necessarily quantitative agreement with the altitude and brightness expected from the characteristics of the measured electron energy spectra. Plain Language Summary: The MAVEN spacecraft has been orbiting Mars since September 2014 to study its upper atmosphere, ionosphere, and interaction with the solar wind. We focus on the discrete aurorae, previously discovered from the Mars Express orbiter. Discrete aurorae are observed on the nightside and are localized both in space and time. We analyze the ultraviolet spectra observed at the limb with the Imaging Ultraviolet Spectrograph to determine the main characteristics of these aurorae. We show that the emission peaks occur at ∼130 km. They are composed of several emissions, such as CO, CO2 +, N2, and atomic oxygen. We find that they occur more often in the presence of strong crustal magnetic field. We also deduce that the altitude of the aurora is independent of many parameters except for seasons. We analyze the intensity ratio of these emissions and show that anomalies occur in the ratio of the CO Cameron bands to the CO2 + UV doublet at low intensity. Finally, we compare the detection of auroral events with the presence of strong electron precipitation measured on board MAVEN. A temporal correlation is generally observed but association of the electron flux and specific UV auroral detection is not always clear because measurements are not colocated. Key Points: N2 Vegard‐Kaplan bands have been detected in the ultraviolet Martian aurora The presence of crustal magnetic field does not influence the altitude of the auroral emission peak Green line intensities up to a few kilorayleighs are expected in regions of crustal magnetic field and may be visible with the naked eye